BEEPO (Social Distancing Tool For Kids) / Dini Sofia Kamarul Sham and Norarifah Ali - Kamarul Sham, Dini Sofia; Ali, Norarifah (Faculty of Art and Design, 2021)
Children are used to the atmosphere of playing, touching and sharing which make it difficult for them to practice a new norm culture of ‘social distancing‘ in their lives. According to the Ministry of Health (MOH) said that it classifies children below 12 years as ‘‘high risk‘‘ for Covid-19 transminssion. As we all know, kindergartens and childcare centers were allowed to start their operation started from May 12, 2020 after the MCO ended and being replaced with CMCO. However, the government will make changes from time to time to ensure the safety of the children. If the Government has allowed the kindergarten to be fully operated, how can the school ensure that these children can practice social distancing among them? Of course, children are easy to adapt to whatever information has been delivered to them but their instinct will tend to forget the rules of social distancing when they started to mingle around and play with their friends This is where the idea of the product came from. BEEPO is a tool that helps to educate the kids to practice social distancing in their lives. This product is specially designed like a toy which mainly intended for use by children, though maybe marketed to adults.